Company Fundamentals as Determinants of Firm-Level Equity Premiums: Evidence from an Emerging Economy - Imran, Muhammad (Panoeconomicus, 2021)
Equity premium is a vital number to consider in finance when making fund allocations and investment decisions. This study explores the relationship between (controllable) determinants of firm-level equity premiums in the context of the Pakistan stock market. It uses a sample of 306 firms’ annual data, from January 2001 to December 2015, using a two-stage least-squares method to estimate our panel data model (Wooldridge 2005; Arellano 2016). During the selected sample period, the average market premium of the Pakistan stock exchange (100 Index) was 20%. The average equity premium of individual firms was only 8%. Company fundamentals are considered determinants of firm-level equity premiums. Panel data econometrics techniques were used to estimate the modified version of the multi-factor model for the Pakistan Stock Exchange. It is found that the market premium, return on equity, dividend payout ratio, accounts receivable and firm size significantly and positively affect the firm-level equity premium. However, increase in the debt-to-equity and quick ratio negatively affect that premium. The company fundamental variables are controllable for the firms and can be improved by company management to encourage investors and maximize shareholder wealth. Key words: Pakistan stock exchange, Equity premium, Company fundamental, Multi-factor model. JEL: B15, B21, B22, C38, E4, E6, G12.